REDUCING CANCER DISPARITIES IN KANSAS: THE ROLE OF POLICY, PREVENTION, AND COMMUNITY HEALTH WORKERS - Waren, Olivia (My University, 2025)
The Kansas Department of Health and Environment (KDHE) is actively working to improve cancer prevention and treatment across the state, particularly in rural communities. Through initiatives like the Kansas Cancer Prevention and Control Plan, KDHE is increasing access to cancer screenings, promoting public awareness, and supporting healthcare providers. However, despite these initiatives, rural cancer disparities remain a significant challenge, as shown by the fact that patients in these areas experience higher mortality rates and poorer health outcomes compared to those in urban areas. These disparities are caused by a multitude of factors, including geographic isolation, limited access to specialized care, and financial barriers. Many rural residents live hours away from the nearest cancer center, making it difficult to receive timely treatment or participate in clinical trials. Additionally, financial constraints, such as higher rates of uninsured individuals and the lack of Medicaid expansion in Kansas, limit access to early detection and preventive care. Healthcare workforce shortages further worsen the problem, as fewer oncologists and specialists are available in rural areas, which leads to delays in diagnosis and treatment. Addressing these disparities requires an interdisciplinary approach. Expanding the role of Community Health Workers has shown promise in improving screening rates and connecting patients with culturally sensitive resources. Increased investment in rural cancer research can ensure rural communities benefit from advancements in precision oncology. And finally, policy changes, including the Rural Hospital Support Act and Medicaid expansion, have the potential to strengthen rural healthcare infrastructure and improve healthcare access. Moving forward, the future of rural cancer care in Kansas will depend on investment in prevention, research, and policy reform. By addressing the disparities in rural healthcare, Kansas can work toward a future where all residents—regardless of where they live—have access to the cancer care they need.
Keywords: Cancer; Rural health; Healthcare policy; Health disparities; Community health workers; Kansas department of health and environment